2017
DOI: 10.1186/s12863-017-0536-0
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics in multiplicity of Plasmodium falciparum infection among children with asymptomatic malaria in central Ghana

Abstract: BackgroundThe determinants of malaria parasite virulence is not entirely known, but the outcome of malaria infection (asymptomatic or symptomatic) has been associated with carriage of distinct parasite genotypes. Alleles considered important for erythrocyte invasion and selected as candidate targets for malaria vaccine development are increasingly being shown to have distinct characteristics in infection outcomes. Any unique/distinct patterns or alleles linked to infection outcome should be reproducible for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 43 publications
2
11
2
Order By: Relevance
“…e study showed a moderate-to-high P. falciparum allelic diversity with the 3D7 allelic family being the most predominant variant circulating in the study communities ( Figure 2). is is similar to data reported from other regions of Ghana and countries in sub-Saharan Africa with similar malaria transmission settings [29,[31][32][33]. A study conducted in the south of Benin however reported the FC27 family as the most predominant allelic family [34].…”
Section: Discussionsupporting
confidence: 89%
“…e study showed a moderate-to-high P. falciparum allelic diversity with the 3D7 allelic family being the most predominant variant circulating in the study communities ( Figure 2). is is similar to data reported from other regions of Ghana and countries in sub-Saharan Africa with similar malaria transmission settings [29,[31][32][33]. A study conducted in the south of Benin however reported the FC27 family as the most predominant allelic family [34].…”
Section: Discussionsupporting
confidence: 89%
“…The sizes of the msp 1 and msp 2 alleles ranged from 120 bp to 350 bp and 150 bp to 600 bp respectively (Table 2 ) and were similar to that previously reported from Gezira State in Central Sudan and in Kolla-Shele area in Southwest Ethiopia where the band sizes for the msp 1 and msp 2 alleles ranged from 150 to 300 bp for KI, 100–300 bp for RO33, 100–380 bp for MAD20, 250–750 bp for 3D7 and 200–700 bp for FC27 [ 56 58 ]. An earlier study conducted in Kintampo in central Ghana identified msp 2 alleles with as high as 900 bp [ 28 ], which were not encountered in this study. This suggests that different P. falciparum parasites circulate in central and southern Ghana, which is not surprising as parasite diversity has been suggested to be constantly changing and distinct in different individuals, populations and seasons [ 10 , 59 ].…”
Section: Discussioncontrasting
confidence: 52%
“…The approximate 1:1 ratio of 3D7:FC27 msp 2 alleles circulating in Obom across the different seasons (Fig. 4c ) seems to be a characteristic of parasites circulating in high transmission settings as a similar ratio was observed in Kintampo, a high transmission setting in Ghana between 2009 and 2010 [ 28 ]. The 3D7:FC27 ratio of 3:2 in Abura was similarly constant across the different seasons, except for in October (Fig.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations